2006
DOI: 10.1002/j.2048-7940.2006.tb00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue After Stroke

Abstract: Fatigue is common and persistent in stroke survivors, yet it is not known how mobility deficits, fitness, or other factors, such as social support, relate to fatigue severity, or whether subjective fatigue contributes to reduced ambulatory activity. The severity of fatigue in a sample of 53 community-dwelling subjects with chronic hemiparetic stroke was examined, and relationships among fatigue and mobility deficit severity, cardiovascular-metabolic fitness, ambulatory activity, social support, and self-effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 25 publications
(35 reference statements)
6
83
0
1
Order By: Relevance
“…One (n=84) found that higher level of fatigue was associated with less standing and stepping but more sitting and lying during the day in patients 1 month after stroke. 46 Another (n=32) found no significant difference in scores of daily activities between fatigued and nonfatigued patients 3 months after stroke. 47 …”
Section: Behavioural Factorsmentioning
confidence: 91%
See 1 more Smart Citation
“…One (n=84) found that higher level of fatigue was associated with less standing and stepping but more sitting and lying during the day in patients 1 month after stroke. 46 Another (n=32) found no significant difference in scores of daily activities between fatigued and nonfatigued patients 3 months after stroke. 47 …”
Section: Behavioural Factorsmentioning
confidence: 91%
“…Michael 2006 (n=46) 46 : higher level of PSF was associated with lower level of social support in patients who were at least 6 months after stroke.…”
Section: Social Supportmentioning
confidence: 99%
“…11 Poststroke fatigue often poses a barrier to return to work and reduced physical function, daily activities, quality of life, and rehabilitation potential. 2,3,9,[12][13][14][15][16][17] Fatigue is associated with profound deterioration of several aspects of everyday life 1,18 and poor poststroke neurological recovery. 19 In a populationbased Swedish 2-year stroke follow-up study, 18 fatigue independently predicted decreased functional independence, in-stitutionalization, and case-fatality.…”
mentioning
confidence: 99%
“…The concept of Frenkel's exercise is to compensate for that loss with the visual system which can update the central nervous system about the position of the limbs in space and their direction of movement, thereby, contributing to balance and improving gait pattern. Detailed administrative protocol of the exercise has been explained elsewhere 15,18 . The ambulatory part of the exercise is the most advanced stage of the exercise and it is characterized by a well-coordinated exercise, with patients required to place their feet in marked footprints as they advance in walking.…”
mentioning
confidence: 99%